Food Systems, Nutrition and Public Health Outcomes: An Integrated Perspective - Anitha S; Shivabasappa Kandkur; Deepa Pujar (Public Health, 2026)
Food systems encompass the full spectrum of activities and actors involved in the production, processing, distribution, consumption, and disposal of food. Their structure and functioning exert profound influences on dietary patterns, nutritional status, and population health outcomes. In recent decades, global food systems have undergone rapid transformation driven by urbanization, economic growth, technological advancement, and globalization. While these changes have improved food availability and reduced hunger in many regions, they have also contributed to new challenges, including the rising prevalence of obesity, diet-related non-communicable diseases (NCDs), environmental degradation, and persistent inequities in access to nutritious foods. This review provides a comprehensive and integrated analysis of the relationships between food systems, nutrition, and public health outcomes. It examines how different components of food systems shape dietary behaviors and nutritional quality, highlighting both positive contributions and adverse consequences. The paper explores key issues such as the dual burden of malnutrition, the environmental impacts of food production, the role of ultra-processed foods, and the implications of globalization and market dynamics. Particular attention is given to vulnerable populations, whose nutritional outcomes are disproportionately affected by systemic inefficiencies and inequities. The review further discusses policy frameworks and intervention strategies aimed at transforming food systems to support healthier and more sustainable diets. Approaches such as the One Health framework, sustainable dietary guidelines, and multisectoral governance are emphasized as critical for addressing complex and interrelated challenges. Innovations in food technology, supply chain management, and agricultural practices are also examined for their potential to improve both nutritional and environmental outcomes. The paper concludes that achieving optimal public health outcomes requires a holistic transformation of food systems that integrates nutritional goals with environmental sustainability, economic resilience, and social equity. Coordinated action across sectors, supported by evidence-based policies and informed consumer behavior, is essential to ensure that food systems contribute positively to human health and well-being in the long term.